Biotechnology of Natural Dyes: Obtaining Pigment Biomass from Beta Vulgaris and Zea Mays Ceratina and Production of Cosmetic Products - Valeria Otori Campos; Danny Lizarzaburu Aguinaga; Elmer Benites-Alfaro; Carlos Cabrera Carranza; Jorge Jave Nakayo; Guido Rene Suca-Apaza; Jose Freddy Atuncar Yrribari (Chemical Engineering Transactions)
The cosmetic industry manufactures products that contain substances that produce harmful effects (toxic or carcinogenic) to the consumer's health, softening or moisturizing substances such as MOSH (Mineral Oil Saturated Hydrocarbons) and MOAH (Mineral Oil Aromatic Hydrocarbons) or heavy metals such as lead when ingested through an application on the lips generate allergic reactions or intoxication. To solve this problem, we propose the extraction of natural pigments using Beta vulgaris (beet) and Zea mays ceratina (purple corn) by dehydration and sedimentation methods. Doses of 0.5 g, 1.0, g, and 1.5 g of beet pigment were applied, with 3 g of purple corn pigment in all doses. The results showed a pasty consistency lipstick with a density of 0.85 g/cm³, softening temperature at 71.8 °C, and melting point at 98.5 °C, also identified an area reduction of 28.2% in the mechanical test. It is concluded that natural colorants can be used in beauty and personal care products with the consequent reduction of environmental impact and health effects instead of using colorants based on synthetic chemical products.